METAL COMPLEXES OF NICKEL, PALLADIUM AND PLATINUM WITH PYRAZOLYL PYRIDINE (Biological Sciences - PJSIR, 2002)
The complexes of 2-(Pyrazol-l '-yl) pyridine with Ni (II), Pd(II)  and  Pt  (II)  are  reported.  Stability  constants  were carried out by Job's method of continuou s variation . The complexes were  characterized  on  the basis of analytical  data for metal determination by atomic absorption , elemental analysis, spectroscopic evidence and qualitative analysis by x ray  diffraction.  The  ligand  fonns a  1:1 complex with these metals.